On the social nature of eyes: the effect of social cues in interaction and individual choice tasks - Baillon, Aurelien; Selim, Asli; van Dolder, Dennie (Elsevier, 2013)
In an experimental setting, we applied a dual strategy to better understand the effect of pictures of eyes on human behavior. First, we investigated whether the effect of eyes was limited to interaction tasks in which the subjects’ decisions influenced the outcomes of other subjects. We expanded the range of tasks to include individual choice tasks in which the subjects’ decisions only influenced their own outcomes. Second, we investigated whether pictures of eyes were one of many social cues or were unique in their effect. We compared the effect of pictures of eyes with the effect of a different condition in which we presented the subjects with pictures of other students (peers). Our results suggest that the effect of pictures of eyes is limited to interaction tasks and that eyes should be considered distinct from other social cues, such as reminders of peers. While pictures of eyes uniformly enhanced pro-social behavior in interaction tasks, this was not the case for reminders of peers. Furthermore, the reminders of peers led to more rational behavior in individual choice tasks, whereas the effect of pictures of eyes was limited to situations involving interaction. Combined, these findings are in line with the claim that the effect of pictures of eyes on behavior is caused by a social exchange heuristic that works to enhance mutual cooperative behavior.